A Feasibility Study of Photovoltaic—Electrolysis—PEM Hybrid System Integrated Into the Electric Grid System Over the Korean Peninsula - Kim, Chang Ki; Cho, Hyun-Seok; Kim, Chang-Hee; Cho, Wonchul; Kim, Hyun-Goo (Frontiers in Chemistry, 2021)
A photovoltaic–electrolysis–PEM hybrid model was developed for a feasibility study, and simulations of several scenarios in Korea were performed. The solar irradiance was derived from the University of Arizona solar irradiance based on satellite–Korea Institute of Energy Research model which provides the satellite imagery over the Korean peninsula every 15 min. In Korea, the annual average solar irradiance is 1310 kWh m2 with a maximum of 1440 kWh m2 in 2017. Electricity load and solar irradiance information were used to test the performance model of the photovoltaic–electrolysis–PEM hybrid system for baseload and several peak load shave runs. When the baseload was set at 4200 MW, the total capacity of the PV plants was 58.5 GWp. In contrast, the hybrid system reduced the peak load more efficiently during daytime. In particular, the capacity factor of the PEM system increased in winter because the solar irradiance is relatively weak in that season. These results provide useful insights for the development of control logic models for the PV–electrolysis–PEM system in micro-grid setups.